(3QSGFd MQjej LOGs - (3cQje, ZGOIs ((3GdbGgQIs (3OGQ Ohf ddfTQ hGdJhRjYs, 2017)
(3y JefjoJ Cf JUdfj Jdc GdQSGFd jhkeG,Cf GbQC GdNQjWI LjkOG bHd Cf CNhV GdJLGQH JGFgI CMGQH hMOj aj gPG GdYGde, hdCfj de CLO ef jOdfj Ydi GdWQjb, cJHoJ ddfSGpA QSGFd YnqeG jOhQ OGNd YbdgG hbdHgG, baRJ Hocqd TLGYI ef NGfI GdeQSd Edjg Edi NGfI GdeQSd, CQOJ Cf CYpqHQ Yf dSGf MGd cd GeQCI (B.. (3dJYQa CfgG djSJ hMjOI aj gPG GdYGde GdbGSj, cdfG fYGfj eG JYGfjf jG YRjRJj, dcfpc dG JYQajf Pdc, hShkqjG (B.. (3Sha JDfS Jdc GdcdeGJ YGdec, HYO hdGOI QhM jfRa GdQMe CQHYjf jhkeG, hHYO Cf JehJ QhM fYdf GdMOGO CQHYjf jhkeG CjkVG, TjlA eG aj gPG GdQbe jQHW Hjf GdMjGI hGdehJ,dPdc(B.. (3gPg QSGFdj GdCQHYjf Edjcys
(3eJhGaQ GdWHYI GdJGSYI dYGe (B2017 (3HecJHI eUQ GdYGeI (B- (3aQY GdRGhjI GdMeQGA (B- (3GdecJHI GdeJfbdIs
(3eJhGaQ GdWHYI GdJGSYI dYGe (B2017 (3HecJHI eUQ GdYGeI (B- (3aQY GdRGhjI GdMeQGAs
(3eJhGaQ GdWHYI GdJGSYI dYGe (B2017 (3HecJHI eUQ GdYGeI (B- (3aQY GdRjJhfs
1 2 10 11 12 13
Keywords: (3GdCOH GdYQHjs; (3GdQSGFd GdYQHjIs -- (3eUQs; (3GdbUU GdYQHjIs